Climate-Smart Agriculture: Farmers' Perspectives - Mutamba, M; Mugoya, M (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Transitioning to climate-smart agriculture (CSA) in the African context requires a transformational architecture — a systematic shift away from business as usual and a comprehensive programme for building the adaptive capacity of physical, socio-economic, human and institutional dimensions of farming systems. Manyewu Mutamba of the Southern African Confederation of Agricultural Unions (SACAU) and Mainza Mugoya of the Eastern Africa Farmers Federation (EAFF) argue that African agriculture is long overdue for a radical transformation to increase productivity sustainably. Although new approaches are now needed, productivity should remain the overachieving objective for Climate-Smart Agriculture on the continent.